Marketing strategy : - Walker, Orville C (Irwin, 1995)
This book differs from other marketing management and strategy texts in that it examines in detail how marketing interacts with other levels of strategy and with other functional departments within an organization. Specially, it includes an examination of three sets of relationships: *) The relationships between corporate, business-level, and marketing strategies. First, the book presents a general discussion of the hierarchy of strategies found in most multiproduct organizations, their interrelationships, and the marketer's role in helping to formulate strategies at different organizational level, provides a more specific and unique discussion of business-level competitive strategies and their implications for marketing strategies and actions appropriate for individual products or services within the the business unit. Finally, it examines how those programs should fit the firm's higher-level strategies.*) The relationships betwwen the content of marketing strategies and the strategic environment. The book talks ingeneral terms about how the marketing strategy for a given product or service should fit the characteristics of the market and competitive environment; discusses the marketing strategies and tactics best suited to specific environmental situations, marketing strategies for new entries; examines strategies for growth markets, strategies for mature and declining markets. Finally, global marketing are detailed. *) The relationships between marketing and other functional areas. The book describes each of the marketing strategies appropriate for the particular circumstances; examines in terms of the requirements it imposes on other functional departments such as product and process R&D, production, quality control, logistics, and finance. In addition, the book provides an overview of the functional competencies required to effectively implement different competitive and marketing strategies. It also discusses organizational mechanisms appropriate for coordinating efforts and resolving conflicts across functional areas